2013
DOI: 10.1155/2013/461415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tea (Camellia sinensis) and Olive (Olea europaeaL.) Leaves Extracts on Male Mice Exposed to Diazinon

Abstract: The present study was aimed to evaluate the effects of tea and olive leaves extracts and their combination in male mice intoxicated with a sublethal concentration of diazinon. Exposure of mice to 6.5 mg/kg body weight of diazinon for seven weeks resulted in statistical increases of serum alanine aminotransferase, aspartate aminotransferase, gamma glutamyl transferase, alkaline phosphatase, creatine kinase, creatinine, glucose, triglycerides, and cholesterol, while the value of serum total protein was declined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 31 publications
6
33
0
Order By: Relevance
“…Diazinon, an organophosphrus insecticide, has been widely used in industrial, veterinary, and agriculture practice, that would be potentially an exposure risk to animals and human as well (Larkin and Tjeerdema 2000). Although several investigations about DZN toxicity have been published, little study has been performed about the preventive agents used against such a toxicity and mechanism of their ameliorative action (Larkin and Tjeerdema 2000;Al-Attar and Abu Zeid 2013;Razavi et al 2013;Elmazoudy et al 2011;ElMazoudy and Attia 2012). In the present study, the renal injuries caused by DZN may be caused by the oxidative stress resulted from free radical production.…”
Section: Discussionmentioning
confidence: 66%
“…Diazinon, an organophosphrus insecticide, has been widely used in industrial, veterinary, and agriculture practice, that would be potentially an exposure risk to animals and human as well (Larkin and Tjeerdema 2000). Although several investigations about DZN toxicity have been published, little study has been performed about the preventive agents used against such a toxicity and mechanism of their ameliorative action (Larkin and Tjeerdema 2000;Al-Attar and Abu Zeid 2013;Razavi et al 2013;Elmazoudy et al 2011;ElMazoudy and Attia 2012). In the present study, the renal injuries caused by DZN may be caused by the oxidative stress resulted from free radical production.…”
Section: Discussionmentioning
confidence: 66%
“…Al-Attar and Abu Zeid [181] found that exposure of mice to 6.5 mg/kg body weight of diazinon for seven weeks resulted in statistical increases in serum alkaline phosphatase activity and creatinine level.…”
Section: Olive Tree (Olea Europaea)mentioning
confidence: 99%
“…The solution of olive leaves was filtered, and finally, the filtrates were evaporated in an oven at 40°C to produce dried residues (active principles). Furthermore, these extracts were prepared every 2 weeks and stored in a refrigerator for experimentation (Al-Attar & Abu Zeid, 2013). The polyphenol compounds of olive leaf extract were established by using chromatographic analysis using GC-MS in center lab of Ain Shams University, Faculty of science.…”
Section: Preparation Of Aqueous Olive Leaf Extract and Polyphenol Conmentioning
confidence: 99%